Urban planning and transition management: Rationalities, instruments and dialectics. - Wolfram, Marc (Springer, 2018)
This chapter juxtaposes the transition management approach with the rationalities and instruments of urban planning. Considering the historic evolution and current characteristics of urban planning in theory and practice, it identifies key challenges and opportunities for engaging with transition management. The discussion underlines the added value but also incompatibility of both approaches, and thus the need to create synergies and mutually compensate for critical deficits to effectively perform urban sustainability transformations. This implies to conceive of a dialectic relation between urban planning and transition management, deliberately striving for coordinated independence.
Keywords: Stadtplanung; Planungstheorie; Nachhaltige Stadtentwicklung; Planungsinstrument; Implementation; Strategische Planung; Partizipation; Kooperation; Akteur; Transformation; Stadtraum; Inkrementalismus; Kollaborative Planung